PENGARUH KONDISI STRESS TERHADAP COPING STRESS PADA ATLET PROVINSI KALIMANTAN TIMUR SEBELUM MENGHADAPI PEKAN OLAHRAGA NASIONAL - Ningsih, Maya Fitria (MOTIVASI, 2016)
ABSTRACTThe purpose of this research is to knowns that is there an impact between stress conditions with the tendency of coping stress strategy of athletes in quarantine time. Stress conditions divided into three levels : high, medium, and low. While coping stress strategy used are problem focused coping and emotion focused coping. So there are two impacts that would be tested in this research : 1) stress level with problem focused coping and 2) stress level with emotion focused coping.This research applied to East Borneo athletes that would participating in Pekan Olahraga Nasional XIX 2016. The number of subject in this research are 26 athletes from eight sports that would be compete in Pekan Olahraga Nasional XIX 2016. This research used purposive sampling method because there are several categories determined by the researcher.The analysis technique used in this research is One Way ANOVA. The research result shows that there is no impact toward stress level with the tendency in choosing coping stress strategy. In the impact of stress levwl toward problem focused coping there is 0,055 F value and significant value 0,946 while the impact of stress level toward emotion focused coping there is 0,299 F value and significant value 0,745.